2017
DOI: 10.1136/svn-2016-000057
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the impact of blood pressure variability on neurological outcome after acute ischaemic stroke

Abstract: IntroductionIncreased blood pressure variability (BPV) is detrimental after acute ischaemic stroke, but the interaction between BPV and neuroimaging factors that directly influence stroke outcome has not been explored.MethodsWe retrospectively reviewed inpatients from 2007 to 2014 with acute anterior circulation ischaemic stroke, CT perfusion and angiography at hospital admission, and a modified Rankin Scale (mRS) 30–365 days after stroke onset. BPV indices included SD, coefficient of variation and successive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
45
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(52 citation statements)
references
References 41 publications
2
45
0
3
Order By: Relevance
“…BP management and its effect on functional outcome is particularly controversial. A previous study showed that increased systolic BPV positively contributed to symptomatic intracerebral hemorrhage and death after intravenous thrombolysis [16]. However, less is known about the effect of short-term BPV after EVT on the early outcomes of AIS-LVO patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BP management and its effect on functional outcome is particularly controversial. A previous study showed that increased systolic BPV positively contributed to symptomatic intracerebral hemorrhage and death after intravenous thrombolysis [16]. However, less is known about the effect of short-term BPV after EVT on the early outcomes of AIS-LVO patients.…”
Section: Discussionmentioning
confidence: 99%
“…The mean age was 64.8±10.9 years, and 27 (37.5%) were women. The median NIHSS score at admission was 14 points [IQR, [9][10][11][12][13][14][15][16][17][18][19], while the median ASPECTS was 8 points [IQR, [7][8][9]. Of the 72 patients, 86.1% patients achieved recanalization (TICI 2b or 3).…”
Section: Patient Demographics and Clinical Characteristicsmentioning
confidence: 99%
“…In another study, de Havenon et al examined the relationship between SD, CV, and SV of SBP measured within 120 hours after admission in 110 patients with acute anterior circulation ischemic stroke with mRS score between 30 and 365 days [55]. Higher BPV was found to be associated with worse outcome, especially in patients with larger ischemic core volumes (defined as relative cerebral blood flow < 40% and absolute arterial tissue delay > 2 s) and larger hypoperfused volumes (defined as relative mean transit time > 135%).…”
Section: Discussionmentioning
confidence: 99%
“…The relapse frequency depends on the subtype of stroke and is the highest in patients who have suffered from stroke due to embolism of cardiac origin, and in cases of a significant stenosis of the carotid arteries [27]. At the same time, high blood pressure is a high-risk factor for patients in all age groups, which further increases the risk of recurrent stroke [65,66,67].…”
Section: Discussionmentioning
confidence: 99%